Assessing Financial Risk and Regional Macroeconomic Influence to Islamic Rural Bank Performance - Faaza Fakhrunnas; Mochamad Ali Imron (Global Review of Islamic Economics and Business, 2019)
Islamic Rural Bank must deal with internal and external risks which will affect to the performance of the bank. This paper aims to assess the internal and external risks that influence to the bank performance. By adopting panel data analysis, the paper analyzes 21 biggest Islamic rural bank which as a representative of 21 provinces around Indonesia during 2013-2017 which result 420 observation period. Furthermore, Return on Asset (ROA) are utilized as dependent variable which represents Islamic rural bank’s performance. As independent variables, Non-Performing Financing (NPF) and Capital Adequacy Ratio (CAR) are applied as internal risk in Islamic rural bank. To analyze external risk, regional macroeconomic factors, Regional Economic Growth (REG) and Regional Inflation (RInf) are employed then Total Asset of Islamic rural bank  (Size) is also used as complementary variable.  Based on the analysis, this study finds that SRB has robust risk management through internal and external risk. However, REG has significant ROA that explains the performance of Islamic rural bank will depend on regional economic growth in each province.